The effectiveness of ayurvedic oil-based nasal instillation (Nasya) medicines in the treatment of facial paralysis (Ardita): a systematic review. (April 2016) - Vivera, Manuel Joseph; Gomersall, Judith Streak
EXECUTIVE SUMMARY: Background: Ardita (facial paralysis) is a medical condition that disfigures or distorts the facial appearance of the sufferer causing facial asymmetry and malfunction. Ardita patients may benefit from considering alternative treatments such as Ayurveda, including Taila Nasya (nasal instillation of medicated oil). Objectives: To synthesize the best available evidence on the effectiveness of different Nasya oils in the treatment of Ardita. Inclusion criteria Types of participants: Studies conducted on adult sufferers (18–70 years) of Ardita (chronic or acute) in any setting were considered. Studies including participants who were pregnant or suffered allergic rhinitis, fever, intracranial tumor/hemorrhage and bilateral facial palsy were excluded. Intervention(s)/comparator(s): Standalone treatment of Nasya (at all dosages and frequencies) compared to Nasya in combination with other Ayurvedic treatments was considered. Comparisons between different interventions including Taila Nasya alone, Taila Nasya in combination with other Ayurvedic interventions and Ayurvedic interventions that did not include Taila Nasya were also considered. Outcomes and measures: Changes in Ardita symptoms, including facial distortion, speech disorders and facial pain, were measured. Types of studies: All quantitative study designs (experimental, quasi-experimental and observational) were considered. Search strategy: Relevant studies were identified following a comprehensive literature search. References provided within these key studies identified additional resources. Indian universities were also contacted for results of Ardita studies undertaken in their institutions. A three-step search strategy aimed to find studies of published and unpublished studies was undertaken. Studies published in the English language were considered for inclusion, irrespective of publication date/year. Following an initial limited search of MEDLINE and CINAHL, the text words contained in the title and abstract, and of the index terms used to describe each articles were analyzed. From the identified keywords and index terms, searches were undertaken across all relevant databases such as PubMed, CINHAL, Cochrane (CENTRAL), Scopus, Centre for Review and Dissemination databases, Turning Research into Practice (TRIP), EMBASE, EBM Reviews, DHARA, Google Scholar, MedNar and ProQuest Dissertations. Finally, reference lists of identified theses and articles were searched for additional studies. Universities and website operators related to Ayurvedic research in India were contacted, including the National Institute of Ayurveda for relevant studies. Besides this, the University of Adelaide librarian was contacted to retrieve those studies identified in the reference lists of theses and articles. Methodological quality: Studies were critically assessed by the review author and a secondary reviewer prior to inclusion in the review using the standardized critical appraisal instrument from the Joanna Briggs Institute. Data extraction: Data was extracted by the primary reviewer using the standardized data extraction tool from the Joanna Briggs Institute. Data synthesis: Different interventions and comparators across studies precluded meta-analysis. Narrative synthesis was performed. Results: Only two pseudo randomized studies with a small number of participants met inclusion criteria and were included in the review. One study with 20 participants, divided equally into two groups compared the effectiveness of two nasal instillations in alleviating four Ardita symptoms. The second study of 15 participants each in two groups compared the effectiveness of nasal instillation with placement of medicated oil on the head on seven Ardita symptoms. Observational measurements of Ardita symptoms were graded as Mild, Moderate or Marked at baseline and after one month. The study conducted on 30 participants using Nasya intervention showed participants had better relief from the symptoms of facial pain, speech disorder and earache within the range of 78.2% to 90.9%, graded as Marked. Along with statistical data available in the studies, this review found low levels of evidence favoring Taila Nasya intervention. The review did not include any studies examining effectiveness of Nasya compared to conventional treatment for Ardita. Conclusions: This review presents extremely limited evidence from only two small experimental studies that administration of Nasya oil alone may provide some relief from Ardita symptoms of facial distortion, speech disorder, inability to shut eyelids/upward eye rolling and dribbling of saliva in adult patients. No strong conclusions may be drawn from the evidence included in the review due to the limited number of studies, limited number of participants and poor quality of studies. Implications for practice: Practitioners should advice Ardita patients that there is extremely limited evidence suggesting the potential effectiveness of Nasya oils alone or Nasya in conjunction with other Ayurvedic treatments in managing symptoms. However, given the absence of a strong evidence base, practitioners should be guided by clinical wisdom and patient preference. Implications for research: Well controlled clinical trials comparing standalone Nasya therapy to other Ayurvedic treatments and/or conventional medicine for Ardita symptoms need to be conducted to examine the relative effectiveness of different Nasya oils in treating Ardita.